STUDY ON THE FEASIBILITY OF VENEER AND PLYWOOD PRODUCTION OF Hevea brasiliensis – CLONE RRIM600 - Raia, Renan Zunta; Iwakiri, Setsuo; Trianoski, Rosilani; de Andrade, Alan Sulato (Floresta, 2022)
Hevea brasiliensis is a very prominent species in Brazil, but there are few studies correlating this species with wood panels production. Based on this, the aim of this work was to evaluate the technical feasibility of laminating and plywood production of Hevea brasiliensis varying the weight and solids content of the glue mixture on the mechanical properties. Phenolic plywood with five 2.0 thick veneers was produced in the laboratory, with two different solids contents of the glue mixture: 35 and 40%, and three different glue weights: 140, 160 and 180 g/m2. The panels were pressed for 10 minutes at 140°C on pressure of 10 kg/cm2. The laminate yield, basic density, and resistance of the glue line to shearing and static bending were evaluated. The lamination yield showed satisfactory results. The lower weight panels produced do not meet the minimum requirement of EN 314-2 and the others two had statistically equal means, and the use of 160 g/m² weight is recommended. The solids content of the glue mix influenced the mechanical properties, but the results still higher than those obtained for Pinus taeda. The results of this study indicate the potential for using Hevea brasiliensis in veneers and plywood production.